Dilemas da produção de conhecimento no campo acadêmico: entre especialização e difusão - Ventura, Mauro de Souza [UNESP] (My University, 2012)
The paper explores some issues related to the production of knowledge in the academic fi eld, relating it to the problem of knowledge dissemination beyond this restricted universe. Taking on theoretical sources from Bourdieu’s fi eld concept and his studies concerning the university fi eld in the work Homo academicus, seeks to examine, in an exploratory approach, the operation modes from academic and diffusion fi elds, opposing the actions from so-called experts and intellectual media, or intermediaries.

O artigo estuda algumas questões relacionadas à produção do conhecimento no campo acadêmico, relacionando-a ao problema da disseminação do saber para além deste universo restrito. Tomando como fontes teóricas o conceito de campo de Bourdieu e seus estudos sobre o campo universitário na obra Homo academicus, busca-se examinar, em abordagem exploratória, os modos de funcionamento dos campos acadêmico e da difusão, contrapondo as ações dos especialistas e dos chamados intelectuais midiáticos, ou intermediários.
Problems of the production of knowledge in the academic field: between expertise and difusion
Keywords: Knowledge; Science; Writing politics; Field concept; Pierre Bourdieu; Conhecimento; Ciência; Políticas da escrita; Conceito de campo; Pierre Bourdieu